MANAJEMEN INSIDEN KEAMANAN CYBER DI DOMAIN PENERBANGAN - Zulkarnaim Masyhur (AMIK Mitra Gama, 2022)
Cyber Security Incident Management has an important role in the aviation domain. Information sharing between air traffic control (ATC) and ground traffic management (GTM) is System Wide Information Management (SWIM), which causes the need for the concept of cyber security management in the aviation domain. Current studies are limited to studying the needs and solutions to improve these capabilities. So, there is a great need for cyber security incident management in a system-wide information management (SWIM) system in the future. This study is a review of the literature. The author conducted a search for references related to the security of privacy data. A method for evaluating, evaluating, and synthesising the results of research works and ideas produced by researchers and practises that is systematic, explicit, and explicit. The main purpose of implementing System Wide Management is to empower the business from the traffic management that will be generated by ensuring the regularly regulated data management is delivered to the ideal individual at the right time. risk management to be able to minimise various obstacles that may occur during the execution of the project. Risk is generally defined as the combination of the likelihood of an event and its consequences (ISO Guide 73). The point is that the business target is not being met. COBIT 5 for Risk characterises IT risk as a business risk, particularly business risk related to the utilization, operation, inclusion, impact, and acceptance of IT in a business. It has described the cybersecurity incident management scheme in the domain based on existing standards and good practices. It is hoped that this can be applied in the aviation domain in the future. This led to an increase in the broad concept of information systems management services. So that it can be a reference for improving incident management in the aviation world and as a reference for research related to cyber security in the aviation world.